2019
DOI: 10.24252/al-mashrafiyah.v3i2.10037
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Strategi Galeri Investasi Syariah Dalam Meningkatkan Minat Mahasiswa Untuk Berinvestasi Di Pasar Modal Syariah

Abstract: The level of financial literacy in Indonesia is still low, there are still many millennials who are not familiar with investment in the Islamic capital market. This study aims to explain the management of strategies undertaken by the Islamic Investment Gallery in attracting students to invest and find out the obstacles faced in attracting investors. This study uses a qualitative method with a descriptive approach. Data collection techniques are interviews with management, MNC Securities and investors managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
0
1
2
Order By: Relevance
“…The same thing was stated in research (Aryani, 2018), (Tanusdjaja, 2018), (Aini et al, 2019), which did not find a relationship between investment in the Islamic capital market and literacy. However, this study is different from the research (Malkan, 2022), (Jalari & Marimin, 2020), (Merawati & Putra Semara, 2015), (Syaifullah et al, 2019), (Herawati & Trisna, 2020), (Zaenal Arifin, 2022) which found that students' interest in investing had a positive impact due to literacy.…”
Section: Financial Literacy Of the Academic Community Of Iain Amboncontrasting
confidence: 94%
See 1 more Smart Citation
“…The same thing was stated in research (Aryani, 2018), (Tanusdjaja, 2018), (Aini et al, 2019), which did not find a relationship between investment in the Islamic capital market and literacy. However, this study is different from the research (Malkan, 2022), (Jalari & Marimin, 2020), (Merawati & Putra Semara, 2015), (Syaifullah et al, 2019), (Herawati & Trisna, 2020), (Zaenal Arifin, 2022) which found that students' interest in investing had a positive impact due to literacy.…”
Section: Financial Literacy Of the Academic Community Of Iain Amboncontrasting
confidence: 94%
“…The existence of an investment gallery as a forum for higher education literacy positively impacts students' demand for investment (Mulyadi & Oktapiani, 2020). This finding is corroborated by several other studies (Rinaldo and Puspita, 2021;Syaifullah et al, 2019;Shofwa, 2017;Jalari & Marimin, 2020;Astuti et al, 2018). This condition is different from the existence of an investment gallery at Ambon Islamic State Institute (IAIN Ambon).…”
Section: Introductionsupporting
confidence: 82%
“…Menurut Manan cara termudah bagi nasabah pemula untuk mengenal investasi saham adalah dengan cara menabung saham melalui MNC Gemesin. Seperti yang kita ketahui para mahasiswa masih memiliki ketergantungan secara finansial kepada orangtua, sehingga nominal tabungan dalam MNC GEMESIN dapat disesuaikan dengan kemampuan masing-masing [12].…”
Section: Gambar 1 Asal Instansi Respondenunclassified
“…Dalam kehidupan bermuamalah investasi sebenarnya tidak disebutkan secara jelas di dalam Al-Qur'an, namun ditemukan banyak pedoman di dalamnya tentang tata cara penggunaan harta yang dimiliki sebagai langkah awal untuk memulai suatu usaha tanpa melanggar syariat yang telah ditetapkan. Investasi merupakan suatu pengorbanan terhadap aset kekayaan yang dimiliki pada masa sekarang guna mendapatkan aset yang lebih besar di masa depan (Syaifullah, 2019). Menurut Sunariyah (2011) investasi merupakan penyimpanan suatu dana atau aset kepada sebuah perusahaan yang umumnya mempunyai kurun waktu yang panjang demi memperoleh keuntungan yang maksimal pada masa depan.…”
Section: Investasiunclassified